Zum Zusammenhang von Einstellungen zum inklusiven Mathematikunterricht mit selbstberichteten Praktiken von Lehrkräften (mathematica didactica, 2023)
Inclusive mathematics teaching is often challenging for secondary school teachers. As their different inclusion-related attitudes and beliefs can be decisive for professional action, they are investigated in this study by means of interviews. Additionally, self-reported teaching practices in inclusive mathematics teaching are reconstructed and put in a structural context with the attitudes and beliefs. The analyses show the influence that inclusion-related attitudes and beliefs have on teachers' self-reported practices. Thereby, different perspectives on school-based inclusion and various influencing variables such as experience, location, and type of disability play a role.